2022
DOI: 10.1002/aic.17635
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of the ionic liquid [HMIm][Tf2N] with compressed carbon dioxide

Abstract: The liquid thermal conductivity of the ionic liquid (IL), 1‐hexyl‐3‐methyl‐imidazolium bis(trifluoromethylsulfonyl)amide ([HMIm][Tf2N]), saturated with compressed vapor and supercritical carbon dioxide was measured over three isotherms (298.15, 323.15, and 348.15 K) and pressures up to approximately 20 MPa using a transient hot‐wire technique. Pure [HMIm][Tf2N] thermal conductivity was also measured over a temperature range of 293.15–353.15 K at ambient pressure and with hydrostatic pressure to approximately 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 116 publications
(258 reference statements)
0
11
0
Order By: Relevance
“…A Flucon Fluid Control GmbH thermal conductivity probe employing the transient hot-wire technique is coupled with a high-pressure equilibrium cell to measure the thermal conductivity of the biphasic IL/refrigerant mixtures. A detailed description of the system and the derivation of the governing equation are provided in our previous work, , and an overview is provided here. A transient hot-wire sensor equipped with a platinum wire is used with a high-pressure equilibrium cell that is loaded with an initial amount of IL.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Flucon Fluid Control GmbH thermal conductivity probe employing the transient hot-wire technique is coupled with a high-pressure equilibrium cell to measure the thermal conductivity of the biphasic IL/refrigerant mixtures. A detailed description of the system and the derivation of the governing equation are provided in our previous work, , and an overview is provided here. A transient hot-wire sensor equipped with a platinum wire is used with a high-pressure equilibrium cell that is loaded with an initial amount of IL.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In our previous study, we have shown that the thermal conductivity of CO 2 -saturated [HMIm][Tf 2 N] increases in certain regions of solubility. 10 This phenomenon appears to be due to the increased pressures required to dissolve CO 2 in the IL to a certain composition. Hence, the hydrostatic pressure exerted may cause an increase in mixture thermal conductivity and we have shown for the pure IL thermal conductivity.…”
Section: = [ + ]mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] ILs have their own unique properties that favor for practical applications. 12,13 ILs usually have very low saturated vapor pressure, even under high vacuum conditions, so that environmental pollution caused by volatilization can be greatly avoided. 14,15 ILs have also good thermal and chemical stability, as well as outstanding capacity to dissolve organic and inorganic substances.…”
Section: Introductionmentioning
confidence: 99%
“…New methods have been developed to capture CO 2 efficiently using ILs through chemical interactions 9–11 . ILs have their own unique properties that favor for practical applications 12,13 . ILs usually have very low saturated vapor pressure, even under high vacuum conditions, so that environmental pollution caused by volatilization can be greatly avoided 14,15 .…”
Section: Introductionmentioning
confidence: 99%